PERHITUNGAN HARGA POKOK PRODUKSI DENGAN MENGGUNAKAN METODE FULL COSTING DAN METODE VARIABEL COSTING PRODUK P3XX PADA PT. YUSHIRO INDONESIA - Nursukmawati, Indri; Nurdiansyah, Dian Hakip (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2021)
The research objective was to determine the calculation of the Cost of Production using the Full Costing Method and the Variable Costing of the P3XX Products at PT. Yushiro Indonesia. Data collection was carried out from October 2020 to November 2020. The data obtained were secondary data. Secondary data is data that does not directly provide data to data collectors (through other people or documents). The research method used is descriptive qualitative research methods sourced from data from the PPIC Department. The data were obtained and analyzed by calculating the Cost of Production using the Full Costing and Variable Costing methods. From the results of data analysis from the company, the company uses the full costing method But, as a comparison the data is made using the Variable Costing method. So that the company does not choose the wrong method used in the future. Keywords: Full Costing, Variable Costing, Cost of Production.